Equity valuation of The Loop Co - Mendes, Pedro Morgado (2021)
The Loop Co is a group that started as a single company focused on circular economy through e-commerce. Since then, the single company has become a group with participation in 4 companies, whose main business segments are e-commerce and ICT maintaining its focus on circular economy. With the situation that is present in the world, circular economy, e-commerce and ICT became essential in the life of the people. Therefore, it is of tremendous interest to evaluate a non-listed group that has as main focus the essential segments in the world right now. This evaluation was done by segment (e-commerce and ICT) and considering the group as a whole. To do so, 2 valuation types were carried out, the DCF model and relative valuation. As the 2 models use different tools, the results obtained by them were different. As the group is not listed, the values obtained through relative valuation are regarded as the most relevant, considering the market and the group financial data. It was seen that the group as a whole is performing according to their budget expectations, as the results obtained by the models were very similar. However, it was also possible to see that the segments, especially ICT could be performing better. The value achieved for an IPO of the group was a value between 17,673,519.42€ and 18,771,515.84€. It was concluded that, besides the results of the group being similar to the ones expected, the group should wait before becoming listed, as its segments can still improve their performance.